INDIRECT SELECTION FOR DROUGHT TOLERANCE IN MAIZE THROUGH AGRONOMIC AND SEEDS TRAITS - ABREU, VIVIANE MARIA DE; VON PINHO, EDILA VILELA DE RESENDE; DOS SANTOS, HELOISA OLIVEIRA; CARVALHO, MARCELA RESENDE; NAVES, GLORIA MARIA DE FREITAS; VON PINHO, RENZO GARCIA (International Journal of Maize & Sorghum, 2017)
ABSTRACT - High prolificacy, stay green, and a reduced anthesis-silking interval are among the traits most used for indirect selection for drought tolerance. The objective of this research was to evaluate five maize lines from the maize breeding program of the company Geneseeds Recursos Genéticos Ltda, to drought tolerance, grown at four plant population sizes, 40, 60, 80 and 100 thousand plants ha-1. In these conditions, the following traits were evaluated: prolificacy, stay green and interval between female and male flowering, which are indirectly related to drought tolerance. The physiological quality of seeds and expression of the enzymes alpha amylase, esterase, catalase, superoxide dismutase, alcohol dehydrogenase, malate dehydrogenase, and heat resistant proteins were also evaluated. The experiment was conducted in a randomized block design in a split plot layout. Differences were observed between the lines for all traits analyzed. Lines 63, 64 and 91 showed the greatest yields and prolificacy, and lines 63, 64, 54 and 91 had the lowest intervals between male and female flowering. No effetc of plant population on the physiological quality of maize seeds was detected, and the highest values of germination and seed vigor were observed in lines 64, 44 and 91. Lines 63, 64 and 91 are considered as promising for drought tolerance. Keywords: Zea mays, Abiotic stress, Flowering, Plant population, indirect selection. SELEÇÃO INDIRETA PARA TOLERÂNCIA À SECA EM MILHO POR MEIO DE CARACTERÍSTICAS AGRONÔMICAS E DE SEMENTES RESUMO - Alta prolificidade, stay green, o reduzido intervalo entre florescimento masculino e feminino estão entre os caracteres mais utilizados para seleção indireta para a tolerância à seca. O objetivo nesta pesquisa foi avaliar cinco linhagens de milho do programa de melhoramento da empresa Geneseeds Recursos Genéticos Ltda., quanto à tolerância à seca, cultivadas em quatro populações de plantio, 40, 60, 80 e 100 mil plantas ha-1. Nessas condições foram avaliados os seguintes caracteres indiretos relacionados à tolerância à seca: stay green, prolificidade, intervalo entre os florescimentos feminino e masculino. Foi avaliada também a qualidade fisiológica das sementes e a expressão das enzimas alfa amilase, esterase, catalase, superóxido desmutase, álcool desidrogenase, malato desidrogenase e proteínas resistentes ao calor. O experimento foi conduzido em delineamento em blocos casualizados, no esquema de parcelas subdividas. Houve diferenças entre as linhagens para todos os caracteres analisados. As linhagens 63, 64 e 91 foram as que apresentaram maiores valores de produtividade e prolificidade e nas 63, 64, 54 e 91 foram observados os menores valores de intervalo entre os florescimentos masculino e feminino. Não houve a influência das populações de plantas sobre a qualidade fisiológica de sementes de milho, sendo que os maiores valores de germinação e vigor foram observados em sementes das linhagens 64, 44 e 91. As linhagens 63, 64 e 91 são consideradas promissoras quanto à tolerância à seca. Palavras-chave: Zea mays, Estresse abiótico, Florescimento, População de plantas, Seleção indireta.